Self-Responsibility for Legal Rights and Freedoms: A Perspective of Fiqh and the Universal Declaration of Human Rights - Rusmana, Dian; Arifin, Tajul; Fauzia, Ine (State of Islamic Institute Langsa, 2025)
Ideally, every individual holds a balanced responsibility toward their rights and legal freedoms, as guided by Islamic Fiqh and the Universal Declaration of Human Rights (UDHR). However, in reality, imbalances between the exercise of rights and responsibilities often occur, both in social and legal contexts. This study aims to analyze the concept of individual responsibility toward rights and legal freedoms from the perspectives of Islamic Fiqh and the UDHR, as well as to identify the common ground between these two perspectives. This article falls under normative research with a qualitative approach, utilizing analysis of relevant primary and secondary literature. The findings reveal that both Islamic Fiqh and the UDHR emphasize a balance between rights and responsibilities, although differences exist in principles and contexts of application. These findings underscore the importance of harmonizing Islamic legal principles and universal norms to achieve social justice.